Implementation of Total Productive Maintenance (TPM) on Mitsui Seiki Compressors to Reduce Production Downtime - Asep Hidayat; Suhendra Suhendra; Yudi Prastyo (Jurnal Ragam Pengabdian, 2026)
This study investigates the application of Total Productive Maintenance (TPM) to improve the performance of the Mitsui Seiki Inverter screw compressor at PT SEI. The research focuses on evaluating the compressor's Overall Equipment Effectiveness (OEE), which combines availability, performance, and quality metrics to assess the effectiveness of the equipment. Data collection involved primary data from observations and interviews with maintenance staff, along with secondary data from production records. The analysis employed TPM techniques, specifically focusing on reducing downtime and improving machine performance by addressing key issues such as nozzle blockages, cooling system failures, and fluctuating speed losses. The results revealed that the average OEE for 2025 was below the ideal standard of 85%, mainly due to performance losses and recurring breakdowns. The study highlights the importance of consistent maintenance, operational parameter control, and enhanced quality control practices. Recommendations include more frequent nozzle cleaning, regular checks of the cooling system, and implementing regular OEE monitoring as a Key Performance Indicator (KPI). The findings provide valuable insights into optimizing the maintenance of industrial compressors and improving overall production efficiency.